Knowledge and behavior of Nigerian dentists concerning the treatment of children with special needs - Sanu Oluwatosin O; Oredugba Folakemi A (BMC, 2006)
Abstract Background Children with special needs (CSN) are reported to receive less adequate dental care due to various behavioral problems and barriers created by dental professionals. This study was carried out to determine the knowledge and behaviour of Nigerian dentists concerning the treatment of CSN. Methods Questionnaires consisting of open and closed ended questions requesting socio-demographic information, type of practice, undergraduate and postgraduate training, self-rated knowledge and behaviour concerning care of CSN, were hand delivered to 359 dentists in the 3 geographical zones of Nigeria over a period of 8 weeks. Responses were compared across age groups, gender, type of practice and training received. Result Two hundred and eighty questionnaires were returned completed, constituting 79.9% response rate. Most of the respondents were aged 30 - 39 years (44.3%). There were more males (56.1%) and more recent graduates of 10 years and below (78.5%). Over 80% of respondents had treated children with disabilities, those with physical disabilities being most encountered. Only 19.3% of respondents rated their knowledge of management of CSN as adequate, with no significant difference across age groups and gender, but with a significantly higher number of older graduates reporting to have adequate knowledge (p < 0.05). Those who had undergraduate training in care of CSN were 69.5% compared with only 12.8% who had post graduate training. Only 11.8% rated their undergraduate training as adequate. Thirty seven percent of respondents rated the CSN they had treated as very challenging. A higher proportion of older graduates (of more than 10 years post graduation) and those who rated their undergraduate training as inadequate used sedation and general anaesthesia. Seventy one percent of respondents were willing to treat CSN, with no significant difference across age groups, gender and training, but with a significantly higher percentage among those who had rated their knowledge as adequate. Most of those who were unwilling to treat CSN felt their management was tedious and challenging. Conclusion From this study, very few dentists reported to have adequate knowledge of management of CSN, irrespective of age, gender and place of practice. A significant number of those with more experience rated their knowledge as adequate. Although most dentists rated the children's behaviour as challenging, they indicated their willingness to treat them in their practices.